Design and performance analysis of a Biplane-Inspired Monocopter (BIM) produced via FDM additive manufacturing process. (2022) - Suhadi, Brian Leonard; Win, Shane Kyi Hla; Win, Luke Soe Thura; Foong, Shaohui
Abstract: The paper presents the first Biplane-Inspired Monocopter (BIM). The novelty of BIM lies on the staggered second wing above the main wing increasing the aspect ratio for a given maximum wingspan. According to General Biplane Theory, this theoretically reduces the induced drag and creates more lift area. Fused Deposition Modelling is instrumental in producing the upper wing. The experiment is conducted autonomously using a closed-loop PID control in an OptiTrack environment. Compared to Single Actuator Monocopter, BIM, which weighs 153 g, requires a lower rotational speed with a minimum of 32.7 rad s −1 while hovering at 1.5 m for 60 s. BIM achieves an average power draw of 28.79 Watt.